Penggunaan Aromaterapi Lavender untuk Meningkatkan Kualitas Tidur Ibu Nifas Pasca Melahirkan Dengan Aromaterapi Lavender - Devina Anggrainy Dencik (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Sleep disturbances are a common complaint among postpartum mothers, and this condition can affect the physical and psychological recovery process after childbirth. Untreated sleep disturbances can lead to various problems, such as fatigue, decreased quality of life, and even the risk of mental health disorders such as postpartum depression. One non-pharmacological approach that can be used to address these sleep disturbances is lavender aromatherapy. Lavender aromatherapy is known to have a calming effect that can help improve sleep quality. This community service activity aims to increase postpartum mothers' knowledge about the use of lavender aromatherapy as a complementary therapy to address their sleep problems. The activity was conducted in June 2025 at the Lismarini Independent Midwife Practice (PMB), using methods that included education, discussion, and distribution of informative leaflets. A total of 15 postpartum mothers participated in this activity, and to measure their knowledge, pre- and post-tests were conducted before and after the education session. The evaluation results showed a significant increase in participants' knowledge levels after participating in the education about lavender aromatherapy. Education about the use of lavender aromatherapy has been proven effective in increasing postpartum mothers' understanding of the benefits and how to use this therapy. Thus, lavender aromatherapy can be a beneficial health promotion strategy to support postpartum recovery. Through this activity, it is hoped that postpartum mothers can apply the knowledge gained to independently improve their sleep quality, thereby supporting their physical and mental health during the recovery period. This activity also contributes to efforts to improve overall public health and provides new insights for healthcare workers in educating postpartum mothers about safe and effective alternative therapies.